2018
DOI: 10.1007/s40430-018-1364-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on sealing capacity of packing element in compression packer

Abstract: Sealing capacity of packing element is of great importance for compression packer. In this study, constitutive experiments and friction experiments of rubber material were carried out. Pressure penetration criterion was applied to numerical simulation model. In addition, a visible indoor experimental setup was established to verify the simulation model. Compressive deformation magnitude and sealing pressure difference capacity of packing element were obtained and compared in numerical simulation and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Therefore, the theoretical maximum contact stress is more conservative than the FEM and experimental solutions, which can effectively predict the change trend of maximum contact stress and provide a lower limit reference value for the contact stress of the packer in the actual seal process. On the premise of allowable contact stress, so long as the theoretical solution meets the sealing requirements, 11 the seal reliability of the actual CPRT structure can be guaranteed.…”
Section: Comparison Of Contact Stress Under Different Axial Loadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the theoretical maximum contact stress is more conservative than the FEM and experimental solutions, which can effectively predict the change trend of maximum contact stress and provide a lower limit reference value for the contact stress of the packer in the actual seal process. On the premise of allowable contact stress, so long as the theoretical solution meets the sealing requirements, 11 the seal reliability of the actual CPRT structure can be guaranteed.…”
Section: Comparison Of Contact Stress Under Different Axial Loadsmentioning
confidence: 99%
“…€ Ongu¨n et al 9 proposed a theory for calculating the Coulomb friction-fluid Reynolds pressure penetration of the rubber ring as a highly deformed dynamic seal, which was closely related to the interaction between the deformed seal structures. Dorokhov et al 10 and Hu et al 11 built an experimental bench, constitutive and friction tests of rubber materials were carried out, and the pressure penetration mechanism was verified. The results showed that the compression deformation and endurable pressure difference increase with the increase of axial loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, in the second step of the local model, the pressure penetration criterion in the FE software is applied to the contact surface, and its principle is shown in Fig. 7 [24,25]. The contact face with elements 3 and 4 is defined as the master surface, and the other surface with elements 1 and 2 is defined as the slave surface.…”
Section: Pressure Penetration Criterionmentioning
confidence: 99%
“…Their results indicated that the packer presented a nonlinear almost elastic mechanical behavior from the second load cycle onwards. For numerical simulation, Hu et al (2017Hu et al ( , 2018, Patel et al (2019a, b) studied the influence of three rubber materials on sealing performance of packing element in the compression packer. Wang et al (2017), Lan et al (2019) studied the structure of the packer rubber with different materials and optimized the structure of its sealing unit.…”
Section: Introductionmentioning
confidence: 99%